Development tracking for model making and rapid prototyping practise based in Industrial Design Education Design Studio / Hasnul Azwan Azizan...[et al.] - Azizan, Hasnul Azwan; Wan Omar, Wan Noor Faaizah; Ali, Norarifah (2018)
This study is conducted to better understand the benefits of the Conventional Model Making (CMP) in Industrial Design learning at higher institutions in today’s industrial innovation. The emergence of technology such as three-dimensional printing (3DP) or Rapid Prototyping in the possess challenges in the design education. This trend changes the conventional ways of making products which indirectly affected the CMP process. The study will focus on how the CMP process is conducted by students and what they can learn from the process compared to the three-dimensional printing (3DP). The researcher will conduct a focus group study to understand this phenomenon.